2018
DOI: 10.11607/prd.3615
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Periodontal Treatment with the Single Flap Approach in Smokers and Nonsmokers

Abstract: The present study was performed to evaluate the impact of smoking status on 6-month clinical outcomes of a regenerative procedure based on enamel matrix derivative and deproteinized bovine bone mineral in the treatment of intraosseous defects accessed with buccal single flap approach. A total of 22 defects were selected in smoking (n = 11) and nonsmoking (n = 11) patients. Regenerative treatment resulted in similar clinical attachment level (CAL) gain in both smokers and nonsmokers. A trend toward lower 6-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 15 publications
1
14
0
5
Order By: Relevance
“…We also analyzed the influence of smoking on clinical outcomes and found no significant differences between smokers and non‐smokers in terms of PDr and CAG, as did in another study of intraosseous defects but unlike others . However, the WC results were significantly worse in smokers ( P < 0.05), as reported by Trombelli et al.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…We also analyzed the influence of smoking on clinical outcomes and found no significant differences between smokers and non‐smokers in terms of PDr and CAG, as did in another study of intraosseous defects but unlike others . However, the WC results were significantly worse in smokers ( P < 0.05), as reported by Trombelli et al.…”
Section: Discussionsupporting
confidence: 60%
“…However, the WC results were significantly worse in smokers ( P < 0.05), as reported by Trombelli et al. (2018) and unlike the results found by Farina et al. (2013), who analyzed WC after a marginal approach to the defect .…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In the present systematic review, we decided to exclude smokers to avoid possible bias considering that smoking affects the wound healing process [85]. Indeed, in a recent clinical study [86] in which the impact of smoking status on the clinical outcomes after regenerative surgical procedures were evaluated, the authors concluded that in smoker patients wound healing quality was significantly hampered when compared to non-smokers. A dose-dependent effect of smoking was observed with respect to the values of PD reduction and CAL gain at 6 months with a tendency to lower values in patients consuming 11–20 cigarettes/day than in smokers from 1 to 10 cigarettes/day.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies focus however on the long-term clinical outcomes after 12 months [76]. In addition, in none of the studies included in the present revision, early wound healing was evaluated with any of the indices/systems already proposed in the literature [23, 24, 86].…”
Section: Discussionmentioning
confidence: 99%